2000
DOI: 10.1063/1.1320028
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of laser-induced cavitation bubbles in liquid nitrogen

Abstract: Initial behavior and the subsequent motion of a bubble in liquid nitrogen are investigated experimentally using high-speed photography. A bubble is generated by focusing a pulsed ruby laser into liquid nitrogen at 78.0 K, changing the ambient pressures up to 253.2 kPa which corresponds to the applied pressure (or overpressure), Δp, being 147.1 kPa. When the energy level of the laser beam at the focus exceeds an irradiance threshold, for instance 5.4×1011 W/cm2 for Δp=4.9 kPa, the optical breakdown occurs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…9 and Bϭ37 MPa which were determined by using the isothermal pressure-density data 16 coupled with the thermodynamic relationships because n is related to the isothermal constant n T multiplied by the ratio of specific heats, (ϭ2.1), namely nϭ n T . According to the definition, sound velocity is given by…”
Section: B Shock Wave Energymentioning
confidence: 99%
See 1 more Smart Citation
“…9 and Bϭ37 MPa which were determined by using the isothermal pressure-density data 16 coupled with the thermodynamic relationships because n is related to the isothermal constant n T multiplied by the ratio of specific heats, (ϭ2.1), namely nϭ n T . According to the definition, sound velocity is given by…”
Section: B Shock Wave Energymentioning
confidence: 99%
“…In a similar manner to the case of water studied by Tomita and Shima, 5 a method using a double-lens-stop system was introduced for generating spherical bubbles in liquid nitrogen. Tomita and his co-workers [6][7][8][9] previously conducted a series of experimental studies of cavitation bubble dynamics, with particular regard to the initial behavior and subsequent motion of laser-induced cavitation bubbles in liquid nitrogen at 78 K. They observed shock waves generated immediately after the plasma formation and found that the sub-sequent bubble shape was nonspherical due to the initial plasma shape but became nearly spherical within a very short period after the bubble initiation. Furthermore, they demonstrated the importance of the inertia of the liquid during the bubble growth, whereas the thermal effect distinctly appeared when the bubble collapsed.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental aspect, the most common method for the investigation of cavitation dynamics behavior is the use of high-speed photography [9,[27][28][29][30]. However, the temporal resolution of high-speed photography is not sufficient to resolve the final collapse phase where bubble splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are also observed for other cryogenic liquids, when use was made of other methods of creating negative pressures. [7][8][9] A liquid under a) Electronic mail: baidakov@itp.uran.ru a negative pressure is extremely sensitive to the presence in it of inhomogeneities (undissolved gases, solid floating particles, poorly wettable sections of the surface of a solid body, etc.) initiating cavitation.…”
mentioning
confidence: 99%